Ammonia volatilization and yield of corn fertilized with different nitrogen sources in the Brazilian semiarid - Santos, Wadson de Menezes; Alves, Bruno José Rodrigues; Urquiaga, Segundo; Pacheco, Edson Patto; Barros, Inácio de; Fernandes, Marcelo Ferreira; Batista, Josimar Nogueira; Bender, Eduardo Pires; Souza, Heraldo Namorato de; Jantalia, Claudia Pozzi (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the effect of the use of different nitrogen fertilizers on N losses by NH3 volatilization and on the grain yield of a corn (Zea mays) crop grown in the semiarid region of the state of Sergipe, Brazil. Corn was managed under rainfed conditions and conventional tillage. The fertilization treatments were: sulfur-coated urea (SU) and organo-mineral-coated urea (OMU). Regular urea and ammonium sulfate (AS) were also included as a reference of N sources of high and low NH3-volatilization potential, as well as a control without N fertilization. The N sources were applied to the soil surface at a rate of 150 kg ha-1 N as side-dressing at the V5 growth stage of corn. The experiment was carried out in 2015 and repeated in 2016. Losses of N through NH3 volatilization differed among the N sources in the two study years, with AS presenting the lowest N losses and regular urea, the highest. In the area treated with OMU, losses by NH3 volatilization were consistently controlled, showing a reduction of 74 and 67% in relation to that of regular urea in both years. SU, however, only mitigated NH3-N losses in 2015, increasing them in 2016, compared with regular urea. Corn plant grain yield and N status, assessed by the index leaf, did not clearly reflect N losses by NH3 volatilization. For the semiarid of Sergipe, OMU is the best urea-based fertilizer to mitigate N losses by NH3 volatilization, and the use of AS is an alternative to increase corn yield and eliminate N losses as NH3.